Local governments, in-kind transfers, and economic inequality - Magne Mogstad; Rolf Aaberge; Lasse Eika; Audun Langørgen (Statistics Norway, Research Department, 2018)
We examine how in-kind transfers provided by local governments affect economic inequality. The allocation of in-kind transfers to households and the adjustment for differences in needs are derived from a model of local government spending behavior. The model distinguishes between fixed and variable costs in production as well as mandatory programmatic spending components versus discretionary spending on different service sectors and target groups. To estimate the model, we combine Norwegian data from municipal accounts and administrative registers for the period 1982- 2013. We find that economic inequality is considerably lower when taking in-kind transfers into account. While the poor benefit from receiving a relatively large share of public services, the equalizing effect of in-kind transfers tends to be smaller than the equalizing contribution from public cash transfers. When examining the time trends in inequality, we find that local governments attenuated the growth in cash income inequality by re-allocating in-kind transfers to low-income families. This reduction in inequality is mostly due to changes in spending priorities across service sectors and target groups, whilst the contribution from re-allocation of resources across municipalities is much smaller.
Keywords: D31; H72; I30; 330; Local government; economic inequality; public services; in-kind transfers